An Assessment to the Mis-Assembled Product Served by Selected Crew at Fast Food Chain in Quiapo: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Crews working in a fast-food chain should be flexible and time management when it comes toservice; therefore, there are missing products, and wrong food orders were given tocustomers due to the mistake of employees assembling food trays the reason they put theythe food to the wrong customers instead to the right one. Still, it is mostly not. All of thecustomers are like that, which will drive customers to complain personally or through sendingemails about their experiences to those negligent service crews in a store, which shows badfeedback towards the service crews and even the image of the store.Fast-food chain A respondents are in the age group of 21-30 years old, while in Fast-foodchain B, they are in the age group of 31-40 years old, both with mostly female respondentsand single. Fast-food chain A respondents are mainly composed of employees, while Bcomprises customers. There are problems encountered with the possible effects ofaccidentally misassembled products in terms of quality service, competitive price,completeness, and cutlery and condiments. Based on the results of the paired two-sample t-test, there is no significant difference between the level of satisfaction with Fast-food A(Jollibee) and Fast-food B (Tropical Hut).Employees working in a fast-food chain should be completely groomed and well-manneredand take notes every time they take an order. Clear speech wording and always repeating theguest order to avoid misassembling that can result in customer complaints should be prioritiesto maintain guest satisfaction. Prioritize and maintain the food they serve with a unique tasteso that the customers will always come back, and If an accidentally misassembled occurs,Management of fast food handles customer complaints very well. Problems encounteredshould be professionally explained by the manager and the employees of a fast-food chain.
Keywords: Business